De-escalated neoadjuvant pertuzumab plus trastuzumab therapy with or without weekly paclitaxel in HER2-positive, hormone receptor-negative, early breast cancer (WSG-ADAPT-HER2+/HR–): survival outcomes from a multicentre, open-label, randomised, phase 2 trial. Issue 5 (May 2022) - Nitz, Ulrike; Gluz, Oleg; Graeser, Monika; Christgen, Matthias; Kuemmel, Sherko; Grischke, Eva-Maria; Braun, Michael; Augustin, Doris; Potenberg, Jochem; Krauss, Katja; Schumacher, Claudia; Forstbauer, Helmut; et al.
Summary: Background: Several de-escalation neoadjuvant strategies have been investigated to reduce the use of chemotherapy in HER2-positive early breast cancer using pathological complete response as a surrogate endpoint; there are few survival data from these trials. Here, we report 5-year survival data in the WSG-ADAPT-HER2+/HR– trial and address the effect of pathological complete response, early therapy response, and molecular subtype. Methods: WSG-ASAPT-HER2+/HR–, a part of the ADAPT umbrella trial performed in patients with different subtypes of early breast cancer, was an investigator-initiated, multicentre, open-label, randomised, phase 2 trial done at 40 Breast Cancer Centres in Germany. Eligible patients were aged 18 years or older with histologically confirmed, unilateral, primary invasive, non-inflammatory early breast cancer, hormone receptor-negative and HER2-positive status, and an Eastern Cooperative Oncology Group performance status of 0 or 1 or a Karnofsky performance status of at least 80%. Patients were randomly assigned (5:2, block size 21, stratified by centre and clinical nodal status) to 12 weeks of either trastuzumab (8 mg/kg loading dose, then 6 mg/kg every 3 weeks) plus pertuzumab (840 mg loading dose, then 420 mg every 3 weeks) or trastuzumab plus pertuzumab plus paclitaxel (80 mg/m 2 weekly); all drugs were administered intravenously. The primary objective of the trial was to compare the number of patients with a pathological complete response at surgery (ie, no invasive tumour cells in breast and lymph nodes [ypT0/is ypN0], the primary endpoint) in early responders (ie, low cellularity or Ki67 decrease ≥30% after 3 weeks) in the trastuzumab plus pertuzumab group versus all patients (irrespective of an early response) in the trastuzumab plus pertuzumab plus paclitaxel group. Non-inferiority was defined as a pathological complete response no worse than 23% lower in the early-responder proportion of patients in the trastuzumab plus pertuzumab group than in the entire trastuzumab plus pertuzumab plus paclitaxel group. The primary endpoint has been reported previously. Additionally, the primary objective of the ADAPT umbrella trial was the evaluation of the effect of pathological complete response on invasive disease-free survival. At investigator's discretion, further chemotherapy could be omitted in patients with a pathological complete response. Secondary survival endpoints were 5-year invasive disease-free survival, relapse-free survival, locoregional relapse-free survival, distant disease-free survival, and overall survival. The effect of pathological complete response on survival was estimated by Cox regression analysis. All analyses are reported in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, number NCT01817452, and is closed to recruitment. Findings: Between March 3, 2014, and Oct 6, 2015, 134 patients were recruited and randomly assigned to treatment, 92 to trastuzumab plus pertuzumab and 42 to trastuzumab plus pertuzumab plus paclitaxel. Median follow-up in survivors was 59·9 months (IQR 53·4–61·4). There were no significant differences between the treatment groups in invasive disease-free survival, relapse-free survival, locoregional relapse-free survival, distant disease-free survival, and overall survival. In the trastuzumab plus pertuzumab plus paclitaxel group and in the trastuzumab plus pertuzumab group, the proportions of patients achieving 5-year survival respectively were 98% (95% CI 84–100) and 87% (78–93) for invasive disease-free survival (hazard ratio [HR] 0·32, 95% CI 0·07–1·49; p=0·15); 98% (95% CI 84–100) and 89% (79–94) for relapse-free survival (HR 0·41, 95% CI 0·09–1·91; p=0·25); 100% (95% CI not estimable) and 95% (88–98) for locoregional relapse-free survival (HR 0·41, 95% CI 0·05–3·75; p=0·43); 98% (95% CI 84–100) and 92% (83–96) for distant disease-free survival (HR 0·35, 95% CI 0·04–3·12; p=0·36), and 98% (95% CI 84–100) and 94% (86–97) for overall survival (HR 0·41, 95% CI 0·05–3·63; p=0·43). Pathological complete response was associated with improved invasive disease-free survival (HR 0·14, 95% CI 0·03–0·64; p=0·011). Two invasive disease-free survival events occurred after a pathological complete response (one in each treatment group). Interpretation: The WSG-ADAPT-HER2+/HR– trial showed good survival rates in patients with a pathological complete response after de-escalated 12-week trastuzumab plus pertuzumab with or without weekly paclitaxel. Omission of further chemotherapy did not affect invasive disease-free survival in patients with a pathological complete response. 12 weeks of weekly paclitaxel plus dual HER2 blockade could be an efficacious de-escalated neoadjuvant regimen in patients with hormone receptor-negative, HER2-positive early breast cancer with high pathological complete response rates and good 5-year outcomes. Further trials of this approach are ongoing. Funding: Roche, Bayer. Translation: For the German translation of the abstract see Supplementary Materials section.